The Structure of Babur's Work "Mubayin" and the Semantics of the Terms Representing the Acts of Hajj and Umra - Taboshar Kadirovich Yuldashev (Journal of Higher Education and Academic Advancement, 2024)
Reading and researching written sources related to the history of the language under study serves as a foundation for the development of that field. Accordingly, the role of "Mubayyin" by Zahiriddin Muhammad Babur in the development of our literary language and national literature is incomparable. The purpose of writing the literary work was to explain the science of Sharia to his son Humayun in a poetic way. By the 15th and 16th centuries, the lexical layer of the old Uzbek literary language was much poorer. Pure Turkic words were replaced by Arabic, Persian and Tajik. This situation kept the masses away from science and enlightenment. This brought the old Uzbek literary language to a crisis. Having correctly understood the process, Babur tried to use pure Turkic words in his works. With this work, Zahiriddin Muhammed Babur contributed to the development of the Uzbek literary language, the history of the Uzbek literary language, the terms, words and expressions of the religious-philosophical spirit of the Uzbek literary language, and the science of Sharia. During the writing of the work "Mubayyin", the author re-used Turkish words that have become obsolete in the history of the Uzbek literary language. Also, he tried to write a work that was convenient, easy and understandable for the student of that time. As a result, "Mubayyin" became very popular among the people in its time.